Pengaruh Brand Image dan Promotion Terhadap Minat Beli di Aplikasi Shopee Pada Mahasiswa Ekonomi Syariah Angkatan 2020 IAI Ibrahimy Genteng - Khoiruddin, Muh.; Sari, Risma Afista Candra (CV. Lentera Literasi Indonesia, 2025)
In this digital era, consumers tend to prefer shopping online rather than offline. This shift influences consumer buying interest and their online shopping habits. Buying interest refers to the desire to own a product. Brand image and promotion play an important role in influencing consumer purchasing decisions. This study aims to determine whether brand image and promotion affect the buying interest of Shopee application users at IAI Ibrahimy Genteng. The research employs a quantitative approach with a causal associative method. The subjects of this study were 43 students of the 2020 cohort from the Islamic Economics Department, who were selected as both the sample and population using a total sampling technique. The research variables include X1 (Brand Image), X2 (Promotion), and Y (Buying Interest). Data were collected through observation and questionnaire techniques. Statistical analysis was conducted using the SPSS program, which included instrument validity and reliability tests, regression analysis, classical assumption tests, and hypothesis testing. The results show that brand image does not have a partial effect on buying interest in the Shopee application among the 2020 Islamic Economics students, with a significance value of 0.525 > 0.05. In contrast, promotion has a partial effect on buying interest in the Shopee application among the same students, with a significance value of 0.001 < 0.05. Simultaneously, both brand image and promotion have a significant effect on buying interest in the Shopee application among the 2020 Islamic Economics students, with a significance value of 0.000 < 0.05.